Corruption as a cultural obstacle when expanding to Western Balkan countries - Saparová, Katarína; Semenenko, Vadim; Martínez Pantoja, Yadira Ixchel; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2023)
Corruption is one of the largest blocks to equality of market opportunities amongst countries and it is mainly caused by the great power of the state administration, lack of transparency, and uncontrolled power of individuals, within the state and business authorities. This issue significantly touches economics, politics as well as ethics. To get a deeper insight into how extensively corruption affects expansion to Western Balkans from the cultural point of view, it is important to understand how this culture accepts corruption and what the relationship is between different cultural dimensions and corruption. Though conducing qualitative research, this paper aims to examine cultural roots and attitudes towards corruption and through analysing different frameworks prevent effective measures to combat corruption in the Western Balkan region. It also explains how historical and cultural factors contribute to the corrupt behaviour.
Vedoucí práce: Vadim Semenenko
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses